Cover Feature: Solvent and Counter‐Ion Induced Coordination Environment Changes Towards AgI Coordination Polymers (Eur. J. Inorg. Chem. 33/2019). Issue 33 (28th August 2019) - Gupta, Arvind Kumar; Salazar, Daniel Morales; Orthaber, Andreas
Abstract : The Cover Feature shows a remote Swedish cabin in a silvery environment guarded by a friendly Viking. The versatility of the tetradentate ligand results in a variety of coordination polymers exhibiting different 1D and 2D topologies. The sun and clouds are composed of a 2D sheet structure with octahedral silver nodes. The small path of the distorted square planar helical polymer leads to the Viking with a square pyramidal silver node at its leash, while the integrity of the tree's stem relies on argentophilic interactions. More information can be found in the Communication by A. Orthaber et al .